Towards an improved framework of e-government implementation in chaotic environment : proposed social collaboration model : case study of Libya - Khamallag, Masoud M (University of Bradford, 2018)
E-government is basically described as using all available electronic media to provide an online public services companies, agencies, citizens or persons in certain country or region. This provision can be provided by the government institutions, agencies, or organisation, in addition to public and private sectors subject to government policies and legislation. Political instability, armed conflict, corruption and chaotic situations are considered to be an obstacle confronting public services delivery and governance in some developing countries around the world. Therefore, Libya is selected a case study of this research. Post the 2011 ousting of the Gadhafi regime in Libya, the country has been experiencing a severe and deep-rooted environment of conflict and chaos, which has destabilised and in some cases dismantled government institutions throughout the country. Within this environment, the original aim of this study was to explore the possibility of implementing e-government services that can provide public services to citizens and, if so, how and what services could be utilised. An exploratory qualitative pilot study was conducted to investigate the feasibility of e-government implementation in Libya utilising the knowledge of government officials. The study found that, the Libyan government had recently and successfully implemented an online e-passport service. An extensive literature review carried out in relation to e-government implementation to help understanding lesions learned and factors behind such success then to utilise the knowledge for further services implementations. Critical success factors of e-government implementation were addressed but available ones are related to stable countries under normal situations. This research is aiming to investigate its implementation in chaotic environment where not much of research is available. During the chaotic environment and instability, different factors may emerge to drive the implementation and the usage of e-services such environment. From government perspectives, it is noticed that cases of corruption, lack of citizens' safety and poor infrastructure were found to be drivers behind the success of existing government institutions and departments of implement e-passport system. Social collaboration and trust in government institutions' commitment were emerged from the citizens' perspectives as factors encouraged the citizens to use the e-passport system. Quantitative data analysed using structural equation modelling techniques using SmartPLS (3.2.7) together with the SPSS 23 were used to analyse the collected data. The outcome were used to propose a framework that can improve the implementation of public e-services while the country at unrest. Another contribution of this studies is the proposal of social collaboration model towards better e-services in such environment.